The Phytochemical Properties and Antidepressant Potential of Satureja Khuzestanica Jamzad Essential Oil in Mouse Models of Depression - Seyed Sepehr Seyedi; Saeid Abbasi Maleki; Ghader Najafi (Tehran University of Medical Sciences, 2023)
Oxidative stress may play a pivotal role in the pathogenesis of depression. Furthermore, antioxidants are also believed to have antidepressant properties. Previous studies have reported the antioxidant effects of Satureja Khuzestanica Jamzad. Therefore, this study examined the antidepressant potential of Satureja Khuzestanica essential oil (SKEO) in male mice based on a forced swim test (FST) and tail suspension test (TST). The GC-MS was used to evaluate the phytochemistry of SKEO. In behavioral studies, 72 male mice were allocated to twelve groups of six and intraperitoneally received the vehicle (10 mL/kg), fluoxetine (20 mg/kg), imipramine (30 mg/kg), or SKEO (25, 50, and 100 mg/kg). Immobility time in TST and immobility, swimming, and climbing times in FST were measured. In the open-field test (OFT), the number of crossings and rearings was recorded. According to GC-MS results, carvacrol, γ-terpinene, cymene, and 2-pinene were the most abundant compounds in SKEO. In FST and TST, all doses of SKEO (except for 25 mg/kg in FST), fluoxetine, and imipramine reduced the immobility time compared to the control group. Moreover, 50 and 100 mg/kg doses of SKEO and fluoxetine increased the swimming time without significantly changing the climbing time. However, imipramine increased the climbing time without significantly changing the swimming time. None of SKEO doses caused a significant change in the number of crossings or rearings in OFT. According to our findings, the antidepressant-like effects of SKEO are similar to those of fluoxetine. While the compounds in SKEO seem to induce their effects through the serotonergic mechanism, further studies are warranted to clarify their exact mechanism of action.